Calculation of fluidization velocities and pressure drop in bubbling fluidized bed gasifier [Cálculo de las velocidades de fluidización y caída de presión en gasificador de lecho fluidizado burbujeante] - Marcelo D. (2017)
This study aims to show the methodology and results related to the calculation of fluidization velocities in a bubbling fluidized bed gasifier. The pressure drops encountered by a fluidizing agent in the particle bed are also exposed. Velocity calculation is important because it enables a good fluidization, which induces a uniform distribution of particles. The good distribution of particles causes a uniform distribution of temperatures in the gasifier where the thermochemical reactions of the process are performed. Biomass functions as a reactor fuel, and accurate fluidization provides a summarized way for correct gasification. Good calculation of pressure drop in the bed is vital for the correctly selecting a blower, a device responsible for providing the power and airflow necessary for fluidization. The bed particles are bauxite with 86% alumina with a density of 2960 kg/m3 and an average diameter of 1.5 mm, the fluidization agent is air, and shredded leaves constitute the spent fuel.